The Effect of Cynometra cauliflora Linn. Fruit Extract-Induced Congenital Anomalies on Chick Embryos - Santiparadon, Manutsanun; Payanglee, Kolip; Somsap, On-Anong; Pengmusaw, Halawatee; Seumae, Kiflanee; Pintarasri, Suriyan (Trends in Sciences, 2024)
Background: Cynometra cauliflora is a traditional folk medicine that is used to treat a variety of unpleasant symptoms without adverse effects. Previous studies have shown that C. cauliflora fruit relieving morning sickness and nausea in pregnant women. However, no research has been performed on the effect of C. cauliflora fruit extract on birth anomalies. Objective: In this study, we aim to investigate the effects of C. cauliflora fruit extract on developing chick embryos. Materials and Methods: Three hundred fertilized eggs were divided into 2 groups; 1) the experimental groups received various doses of C. cauliflora fruit extract at 50, 100, 200, and 400 mg/kg, and 2) the control group received a 0.9 % normal saline solution. One hundred and fifty eggs at embryonic day-3 (ED-3) were observed for LC50, morphology, and histology, while the 150 eggs at embryonic day-6 (ED-6) were investigated for morphology and histology. Results: At a dosage of 291.70 mg/kg, the C. cauliflora fruit extract induced mortality in ED-3 by more than 50 %. Moreover, fruit extraction can also result in anomalies in ED-3 and ED-6, such as anterior neuropore openings, heart tubes, liver and kidney tissue defects. Conclusion: As a result, it was determined that tissue damage and organ malformation followed dose-dependent and all-or-none laws. Despite having a wide range of medical properties, C. cauliflora fruit extracts have been demonstrated to impair early growth and development and cause birth abnormalities in animal studies. This will allow further determination of regulatory criteria for medical use, particularly for pregnant women. HIGHLIGHTS First report of the cauliflora fruit extract induced embryonic lethality The cauliflora fruit extract induces embryonic organ and tissue anomalies following dose-dependent and all-or-none laws These experimental protocols are beneficial for teratogenesis studies GRAPHICAL ABSTRACT